Understanding the lives of caregivers of children with cerebral palsy in rural Bangladesh: use of mixed methods - Zuurmond, Maria A; Mahmud, Ilias; Polack, Sarah; Evans, Jenny (© 2015 Action for Disability Regional Rehabilitation Centre, 2016)
Includes bibliographical references (page 19-21).